2009
DOI: 10.1074/jbc.m109.004648
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Insoluble Rat Sperm Glyceraldehyde-3-phosphate Dehydrogenase (GAPDH) via Heterotetramer Formation with Escherichia coli GAPDH Reveals Target for Contraceptive Design

Abstract: Sperm glyceraldehyde-3-phosphate dehydrogenase has been shown to be a successful target for a non-hormonal contraceptive approach, but the agents tested to date have had unacceptable side effects. Obtaining the structure of the sperm-specific isoform to allow rational inhibitor design has therefore been a goal for a number of years but has proved intractable because of the insoluble nature of both native and recombinant protein. We have obtained soluble recombinant sperm glyceraldehyde-3-phosphate dehydrogenas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 52 publications
3
30
0
Order By: Relevance
“…Residues located in disallowed regions in our structures were found within similar regions in many other GAPDH structures. [19][20][21] Water molecules were added to the present models with Coot. The peak contoured at 1.8r in 2Fo-Fc maps was identified as a water molecule.…”
Section: Structural Determination and Refinementmentioning
confidence: 99%
See 1 more Smart Citation
“…Residues located in disallowed regions in our structures were found within similar regions in many other GAPDH structures. [19][20][21] Water molecules were added to the present models with Coot. The peak contoured at 1.8r in 2Fo-Fc maps was identified as a water molecule.…”
Section: Structural Determination and Refinementmentioning
confidence: 99%
“…GAPDH enzymatic activity requires the binding of NAD but the enzyme shows different binding characteristics depending on the tissue source. [19][20][21][22][23] Here, we present two high resolution crystal structures of GAPDH from ROS with different occupancies of NAD. These GAPDH structures provide an updated view of their NAD-binding sites, and their conformational changes induced by NAD binding.…”
mentioning
confidence: 99%
“…When typical E. coli strains were used for expression, mass spectrometry analyses confirmed that mouse GAPDHS and the host bacterial GAPDH formed mixed tetramers, resulting in the co-purification of bacterial and recombinant enzymes (data not shown). A similar observation has been made for the rat GAPDHS expressed in E. coli with the purified tetrameric enzyme consisting of 3 subunits of E. coli GAPDH and 1 subunit of rat GAPDHS [7]. Our approach was to express recombinant human GAPDHS lacking the proline-rich N-terminal region in a GAPDH-deficient E. coli strain (CGSC strain #7563).…”
Section: Resultsmentioning
confidence: 75%
“…The expression of recombinant GAPDH enzymes in E. coli has met with varied success, with high production of insoluble material frequently observed [9]. A recent study found that expression of rat GAPDHS, either as a full-length protein or a truncated protein lacking the proline-rich N-terminus, resulted in protein that was predominantly insoluble [5]. We have had similar difficulties obtaining high yields of soluble protein when expressing recombinant mouse or human GAPDHS in E. coli.…”
Section: Introductionmentioning
confidence: 99%
“…We have had similar difficulties obtaining high yields of soluble protein when expressing recombinant mouse or human GAPDHS in E. coli. Although native GAPDH enzymes typically function as homotetramers (molecular mass ~150 kDa), the expression of rat GAPDHS in E. coli resulted in mixed tetramers consisting of 1 subunit of rat GAPDHS and 3 subunits of E. coli GAPDH [5]. The generation of GAPDH heterotetrameric forms combining purified GAPDH dimers from two different species has been reported [1011].…”
Section: Introductionmentioning
confidence: 99%